Effects of Adrenaline on maternal and fetal fentanyl absorption in epidural analgesia: A randomized trial. Issue 9 (25th June 2018) - Haidl, F.; Rosseland, L. A.; Spigset, O.; Dahl, V.
Abstract : Background: The combination of low‐dose local anesthesia and lipophilic opioids such as fentanyl is established as a standard solution for labor epidural analgesia. Fentanyl increases efficacy, but may have negative effects on the neonate in terms of reduced neonatal neurologic and adaptive capacity scores and breast feeding. We hypothesized that addition of adrenaline 2 μg/mL to a solution of bupivacaine 1 mg/mL and fentanyl 2 μg/mL would reduce the systemic uptake of fentanyl, resulting in reduced serum fentanyl in the fetus at birth. Methods: Forty‐one nulliparous women requesting epidural analgesia were randomized to epidural analgesia with or without adrenaline. Blood samples were drawn from the mother with regular intervals, and at delivery. An umbilical vein blood sample (used as a proxy for fetal exposure) was drawn after clamping. Results: There were no significant differences between the groups in fentanyl concentrations in the umbilical vein and maternal serum at birth. There was a significantly lower mean area under the maternal serum‐concentration curve for the first 2 hours of treatment in the adrenaline group (mean difference 0.161 nmol h/L [0.034; 0.289], P  = .015), implying slower systemic uptake in the adrenaline group initially. There were no significant differences in treatment duration, motor block, Apgar scores, umbilical pH and base excess, or mode of delivery. Conclusions: The addition of adrenaline to an epidural solution containing fentanyl lowered maternal systemic serum fentanyl concentration during the first 2 hours, but did not lower serum fentanyl concentration in the umbilical vein and mother at delivery.